(untitled) (Research, Society and Development, 2022)
The article aims to present inclusive approaches that result in discussions and debates on the importance of an early diagnosis in favor of an agile and quick intervention of the child with Autistic Spectrum Disorder (ASD) to develop their social interaction and quality of life together with their family. Presenting potential benefits to develop and integrate socially and educationally, starting from the first stage of basic education, early childhood education, presenting treatment possibilities with gains in inclusion, learning, quality of life, health and well-being, which will be aggregated as value and lifelong development. A descriptive and qualitative bibliographic reference method was sought, touching on the relevance and importance for the child to be treated and worked on in their cognitive, affective, sensorial and motor development and to obtain their inclusive independence and quality of life. The content is instructional and qualifying so that professionals and future professionals are aware and encouraged to know and delve deeper into dealing with this public early on, as they lack the correct apparatus and due attention from an early age, given the lack of knowledge and development of methods for early diagnosis and treatment. In conclusion, it is expected that the contents addressed will raise the attention and sensitivity of the professionals most involved in this relationship, so that together they work towards diagnosis and treatment so that there is no lower probability of manifestation of other problems, increasing the potential development of the child individually and collectively, whether in the family, school and society in which he is inserted.